Peran Strategis Kinerja Pemerintah Walikota Bandar Lampung Pada Pengelolaan Sampah Dalam Prespektif Sosiologi Politik - Berchah Pitoewas; Abdul Halim; Serly Pramudita; Indah Septia Lestari; Kayla Zahara Salsabila; Desika Fitriana; Imelda Mauly Jevita; Ria Rahmanisa (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Waste management in Bandar Lampung City faces complex challenges along with rapid population growth. This article aims to analyze the strategic role of the performance of the Bandar Lampung City Government, especially the Mayor, in managing waste through a political sociology approach. This approach uses a deep understanding of the dynamics related to power, public policy, and community participation in the context of waste management. The method used is descriptive qualitative and literature study with participatory observation data collection techniques. The results of the discussion of this article indicate that local government performance is greatly influenced by factors such as political leadership, policy effectiveness, and community involvement. The implementation of effective waste management policies requires synergy between the government, community, and private sector. This article contributes to understanding the importance of the strategic role of local government in waste management and its implications for sustainable development.